2014
DOI: 10.1111/1475-6773.12197
|View full text |Cite
|
Sign up to set email alerts
|

“Phenotyping” Hospital Value of Care for Patients with Heart Failure

Abstract: Objective. To characterize hospitals based on patterns of their combined financial and clinical outcomes for heart failure hospitalizations longitudinally. Data Source. Detailed cost and administrative data on hospitalizations for heart failure from 424 hospitals in the 2005-2011 Premier database. Study Design. Using a mixture modeling approach, we identified groups of hospitals with distinct joint trajectories of risk-standardized cost (RSC) per hospitalization and risk-standardized in-hospital mortality rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…[28] We determined value phenotypes among groups of hospitals, exposing similarities among institutions that, on the surface, did not appear to have much in common. [27,28] The next step is to understand what hidden factors influenced the similar performance.…”
Section: What the Future Could Holdmentioning
confidence: 99%
See 1 more Smart Citation
“…[28] We determined value phenotypes among groups of hospitals, exposing similarities among institutions that, on the surface, did not appear to have much in common. [27,28] The next step is to understand what hidden factors influenced the similar performance.…”
Section: What the Future Could Holdmentioning
confidence: 99%
“…[28] We determined value phenotypes among groups of hospitals, exposing similarities among institutions that, on the surface, did not appear to have much in common. [27,28] The next step is to understand what hidden factors influenced the similar performance. This type of analysis opens the way for investigations of the determinants of these differences, perhaps leveraging methods that have illuminated factors that produce positive deviance and ultimately developing interventions to improve performance.…”
Section: What the Future Could Holdmentioning
confidence: 99%
“…Overall, we are interested in clustering POs in our sample frame according to the trajectories of TCC with the ultimate goal of stratifying the sample according to TCC trajectory shape and level. The literature contains dozens of clustering methods, including some, such as developmental trajectory mixture modeling that have been applied to examining hospital‐level cost and care outcomes . While few, if any, of these methods were developed for sampling purposes any of them could be used to segment the sampling frame for purposes of stratification for sample selection.…”
Section: Methodsmentioning
confidence: 99%
“…Methods for estimating in-hospital cost are detailed elsewhere (3, 13). Briefly, we used accounting cost data available in the Premier database and removed geographic variation in input prices by applying average unit cost across all hospitals for each service item by year.…”
Section: Methodsmentioning
confidence: 99%
“…Using advanced analytics of pattern recognition, recent big data research revealed important similarities and differences among hospitals in provision of care (1-3). In contrast with conventional studies that analyze how hospitals deviate from an average tendency in care, the approach of pattern recognition explores whether there are distinct “phenotypes” among hospitals, representing fundamentally different patterns of care (4).…”
Section: Introductionmentioning
confidence: 99%